Status of Elementary Education in India (International Journal of Scientific Research and Management (IJSRM), 2016)
It is widely accepted that education is an important instrument of social transformation and economic development of the country (Caldwell, Reddy and Caldwell, 1985, Tilak, 2003). Education increases awareness of the society and weakens the social hierarchy which is considered as the main cause of discrimination across social groups in the society. Further, education also reduces economic inequality as earnings and education has a positive relationship. In addition to this, the strong linkages between the educational attainments of population and the economic growth of the country are widely recognized in the literature (Tilak, 2003; Jha, Das, Mohanty and Jha, 2008).